Analysis of sub-synchronous oscillation characteristics of PMSGs based on transient energy - Yan, Gangui; Wang, Yupeng; Yang, Cheng; Yue, Lin (Frontiers in Energy Research, 2023)
Faced with the problem of sub-synchronous oscillation (SSO) caused by the interaction between the permanent magnetic synchronous generators (PMSG)-based wind farm and weak AC grid, we construct a transient energy function model that follows the structure of PMSG. The transient energy composition of PMSG has been analyzed, and the dissipation energy expression that can intuitively reflect the development trend of SSO is derived, reflecting the damping level of grid-connected wind power system. Furthermore, in response to the problem of mutual coupling between the control links of the PMSG during the SSO process which hinders oscillation characteristic assessment, a method based on oscillation energy is proposed to analyse the oscillation characteristics. Considering the dynamic changes in the output of the phase-locked loop during sub-synchronous oscillation, the transient energy dominated by various control links is derived, and the effects of PLL, current inner loop, and voltage outer loop on transient energy and oscillation characteristics have been analyzed.The simulation verifies the effectiveness of the analysis of the transient energy model.